High resolution computed tomographic assessment of asbestosis and cryptogenic fibrosing alveolitis: a comparative study. Issue 8 (August 1992) - al-Jarad, N; Strickland, B; Pearson, M C; Rubens, M B; Rudd, R M
Abstract : BACKGROUND: The aim of this study was to compare the distribution and configuration of lung opacities in patients with cryptogenic fibrosing alveolitis and asbestosis by high resolution computed tomography. METHODS: Eighteen patients with cryptogenic fibrosing alveolitis and 24 with asbestosis were studied. Two independent observers assessed the type and distributions of opacities in the upper, middle, and lower zones of the computed tomogram. RESULTS: Upper zone fibrosis occurred in 10 of the 18 patients with cryptogenic fibrosing alveolitis and in six of the 24 patients with asbestosis. A specific pattern in which fibrosis was distributed posteriorly in the lower zones, laterally in the middle zones, and anteriorly in the upper zones was seen in 11 patients with cryptogenic fibrosing alveolitis and in four with asbestosis. Band like intrapulmonary opacities, often merging with the pleura, were seen in 19 patients with asbestosis but in only two with cryptogenic fibrosing alveolitis. Areas with a reticular pattern and a confluent or ground glass pattern were the commonest features of cryptogenic fibrosing alveolitis (15 and 14 patients respectively) but were uncommon in asbestosis (four and three patients). Pleural thickening or plaques were seen in 21 patients with asbestosis and in none with cryptogenic fibrosing alveolitis. CONCLUSION: Apart from showing pleural disease high resolution computed tomography showed that confluent (ground glass) opacities are common in cryptogenic fibrosing alveolitis and rare in asbestosis whereas thick, band like opacities are common in asbestosis and rare in cryptogenic fibrosing alveolitis.